Legionella disinfection by solar concentrator system. (April 2017) - Amara, S.; Baghdadli, T.; Knapp, S.; Nordell, B.
Abstract: The current study concerns the fundamental problems of Legionnaires disease. Four decades after Legionnaires' bacteria was first identified there is still a low level of clinical awareness. Humans are infected by inhalation of aerosolized water and/or soil contaminated with the bacteria. Several control methods are available for water disinfection: biocide, ultraviolet light sterilization, copper-silver ionization, ozonation etc. but only thermal treatment can completely eliminate Legionella, which is killed almost instantly at 70 °C. The current paper describes Legionella disinfection by a solar concentrator combined with a heat recovery system that reduces the heat demand. Though this study is made for a small system (160 l of hot water per day) the system can be enlarged (more hot water and more solar collector area) and the results are thus valid also for such larger systems. Here experiments of water treatment by a solar concentrator are summarized and analyzed where the temperature exceeds 80 °C at the outlet of the heat exchanger. Highlights: More than 80 °C of hot water has been achieved for bacteria disinfection. ABHE system was built, tested and approved with solar concentrator as heat source for Legionella disinfection. Developed model of the ABHE was simulated and validated.